2016
DOI: 10.7314/apjcp.2016.17.2.851
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Breast Cancer Awareness Scale for Thai Women: Moving towards a Validated Measure

Abstract: Background: Breast cancer is a major health problem among women around the world. Recent developments in screening and treatment have greatly improved the prognosis of patients with breast cancer in developed countries. However, in developing countries breast cancer mortality remains high.Breast cancer awareness is a first and important step in reducing breast cancer mortality. The development of a validated instrument to measure breast cancer awareness is crucial for the understanding and implementation of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…The SEM as a measure of absolute reliability, and the SDC, as a real change greater than the measurement error, were not evaluated for the original English version and for the other translated versions of BCAM; however, the estimated values of SEM and SDC were satisfactory in the current study, which indicates the reliability and responsiveness of the BCAM‐Persian. Accordingly, these indices (SDC and SEM) will be useful in interventional studies for evaluating the effectiveness of intervention.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The SEM as a measure of absolute reliability, and the SDC, as a real change greater than the measurement error, were not evaluated for the original English version and for the other translated versions of BCAM; however, the estimated values of SEM and SDC were satisfactory in the current study, which indicates the reliability and responsiveness of the BCAM‐Persian. Accordingly, these indices (SDC and SEM) will be useful in interventional studies for evaluating the effectiveness of intervention.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have shown that the increased women's awareness about early diagnosis can change people's screening health‐seeking behaviors . Therefore, there is an urgent need for improving great BC awareness and its early detection measures among women . Accordingly, developing and validating of instruments for measuring and monitoring levels of breast cancer awareness and its determinants could be a pivotal approach .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variable was independent in the regression model and showed significant values for all BSE performance categories. In a recent study conducted in Thailand, knowledge of risk factors was identified as a relevant variable for the identification of breast cancer (Rakkapao et al, 2016). Literature points to the importance of different kinds of knowledge for BSE performance: Knowledge about cancer was positively associated with BSE performance in a health-beliefs model (Ardahan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different studies have emphasized that knowledge about the disease and risk factors, as well as the presence of close relatives with breast cancer, may affect women's motivation to perform BSE (Garber et al, 2013;Ardahan et al, 2015;Tilaki and Auladi, 2015;Rakkapao et al, 2016).…”
Section: Knowledge About Risk Factors For Breast Cancer and Having A mentioning
confidence: 99%